Atrophic nodular cutaneous amyloidosis* - Yuan Jiang; Qingtao kong; Yun Hui; Hong Sang (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Primary cutaneous amyloidosis is limited to the skin without involving any other tissue. Nodular amyloidosis is rare, and atrophic nodular cutaneous amyloidosis is even rarer. We describe the fourth case of atrophic nodular cutaneous amyloidosis by searching PubMed databases. A 52-year-old female presented to our hospital with a 2-year history of orange papules and nodules without subjective symptom on her right abdomen. Review of systems was negative. Atrophic nodular amyloidosis may progress to primary systemic disease in up to 7% of cases. Because our patient had no systemic involvement, she was diagnosed with atrophic nodular cutaneous amyloidosis based on characteristic symptoms and histopathologic examination. Routine follow-up for this patient is necessary to detect any potential disease progression.